Eye Care in Young Children: A Parents’ Perspective of Access and Barriers - Ali M Alsaqr (Journal of Ophthalmic & Vision Research, 2023)
Abstract Purpose: To evaluate parental perspectives of accessing eye care for children aged under seven years. Methods: The survey was conducted during September 2020 to March 2021 using online applications and distributed to parents whose children were between the ages of three and seven years. The survey included parents' background, their knowledge of the provision of eye-care services, and the possible barriers that existed to access eye-care services. The relationship between parents' knowledge, barrier scores, level of parental education, and demographic or socioeconomic status was assessed using nonparametric tests. Results: In total, 1037 questionnaires were completed. The respondents were from 50 cities across Saudi regions. The participants' age was 39 ± 7.5 years, and 54% of them had at least one child under the age of seven (n = 564). Further, 47% had not taken their children for vision screening at reception/year one (n = 467). In addition, 65% of them were not aware of the mandatory screening program at reception/year 1; whereas, only 20% (n = 207) knew how to access eye-care services; and only 39% of the children had undergone any kind of eye or vision test. The pathways to eye care and the cost of eye services/glasses were the main limitations. The parents' responses were significantly influenced by their demographic and socioeconomic characteristics (Kruskal Wallis, P < 0.05). Conclusion: There was a need for enhancing parent information on how to access eye care for young children and the currently available vision screening programs. Finally, a national protocol to cover the cost of the eye exam as well as spectacle prescription shall be proposed as a mean of incentive.